Inserción laboral de jóvenes profesionales. El caso de los psicólogos bonaventurianos - Orejuela, Johnny Javier (Editorial Bonaventuriana, Universidad de San Buenaventura Cali., 2021)
The research on labor insertion of young professionals in psychology is made public at a crucial moment for the discipline and the practice of the profession in the country, where the academic community and the professional guild face the very task of inserting psychology as a solid body of theoretical and technical knowledge, in the body of knowledge, resources and devices available to citizens and institutions. As Colombians and according to what the profession allows us, we are part of the social fabric in the framework of the repair and comprehensive reconstruction of a nation that urgently seeks options and actions that bring with them the improvement of the quality of life, greater inclusion and social equity. In short, truly democratized development and progress, so that it corresponds to the individual and collective resources and the optimal use we can make of them, within the framework of opportunities.